Current Technological Trends in Transdermal Biosensing - Yuyue Zhang; Cheng Yang; Haibin Shi; Chenjie Xu (Advanced NanoBiomed Research, 2022)
Transdermal biosensing focuses on the qualitative and quantitative collection and detection of biomarkers on and in the skin layers. In comparison to the blood‐based diagnosis, transdermal sensing technologies provide pain‐free, convenient, patient‐friendly, and infection‐avoiding methods to collect biosignals from transdermal samples such as interstitial fluid (ISF) and sweat. This article summarizes the latest trends in transdermal biosensing including the technologies and their application blueprints. Specifically, the current transdermal biosensing technologies including microneedles, microfluidics, and reverse iontophoresis are introduced first. Subsequently, their roles in daily health status monitoring, disease diagnosis and therapy monitoring are discussed in detail. Finally, an overview of the future blueprints and application prospects of transdermal biosensing is provided.